Energy use in paddy production in Malaysia - Bardaie, Mohd. Zohadie; Wan Ismail, Wan Ishak (1981)
The rapidly increasing price of crude oil has generated a lot of concern over the relationship between energy consumption and agricultural production. In Malaysia, the use of agricultural machinery in agricultural production is certain to continue regardless of the energy situation. The concern over the increasing energy input into the process due to mechanization is overwhelming. Thus, it is advantageous to analyze the energy use at the various stages of the production process. The results could the be used in formulating a strategy on energy conservation in the production process. This paper will focus on the energy use in paddy production in Malaysia. At present, the paddy production process in Malaysia is going through a modernization stage with the introduction of modern agricultural machinery. The form and intensity of the energy input for the various stages of paddy production namely land preparation, nursery operation, transplanting, crop upkeep and maintenance, and harvesting were analyzed and discussed. The various form of energy input will be converted to an equivalent uniform unit of energy for comparison purposes. An economic analysis of the energy inputs in the process with respects to the present energy situation in the country will be briefly discussed. This will include the projected future energy input cost of paddy production in accordance with the future predicted price of crude oil. Available alternative energy inputs in the process will be discussed along with its implication on the effect on Malaysian agriculture as a whole